Beach morphology and sand characteristic at selected recreational beaches along northern region of Pahang coastline - Ramli, Muhammad Zahir; Syafiq Hamsan, Muhammad Amirul (2018)
Smoothed Particle Hydrodynamics (SPH), a fully Lagrangian meshless method, has been used in a wide variety of hydrodynamic problems overcoming the limitation of finite volume and element type methods. In previous work, weakly compressible SPH (WCSPH) has proven to be stable in the prediction of hydrodynamic coefficients of sway, heave and rolling motions. The current research attempt to demonstrate WCSPH in the analysis of diffraction problem by investigating the behaviour of a fixed 2D rectangular section in regular waves. The incoming waves generated by a piston-type wavemaker would encounter the section creating diffraction interference of waves. The interactions between waves and fixed section are shown through transmission of forces from the waves to the section and vice versa. The predicted hydrodynamic forces of horizontal force, vertical force and overturning moment by WCSPH are then analysed and validated against analytical solutions. Finally, a convergence analysis is carried out to identify the suitable particle resolution needed for accurate representation of hydrodynamic forces.